2015
DOI: 10.5539/elt.v8n9p26
|View full text |Cite
|
Sign up to set email alerts
|

Language Teacher Burnout and School Type

Abstract: The present study was an attempt to explore the level of burnout among primary school teachers in Malaysia. In addition, the study tried to determine if the school type has any significant influence on teachers' burnout level. To this end, 714 primary school teachers participated in the study. They were teaching at Malay (SK), Tamil (SJKT), and Chinese (SJKC) medium schools. The Maslach Burnout Inventory-Educators Survey (MBI-ES) (Maslach, Jackson, & Schwab, 1986) was used to collect the data on the teachers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The existing literature on burnout among English teachers in Malaysia depicts that the burnout level is significantly high (Mahboobeh, Mukundan, & Nimehchisalem, 2012;Mousavy & Nimehchisalem, 2014;Mukundan & Khandehroo 2010;Mukundan, Pezhman, Abdolvahed, Umi Kalthom, & Husniah, 2015). Nevertheless, these studies were focusing more on the influence of age, gender, marital status and school type on teacher burn-out, and little analytic attention has been paid to those who serve in rural schools.…”
Section: The Burnout Phenomenon Among Rural English Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature on burnout among English teachers in Malaysia depicts that the burnout level is significantly high (Mahboobeh, Mukundan, & Nimehchisalem, 2012;Mousavy & Nimehchisalem, 2014;Mukundan & Khandehroo 2010;Mukundan, Pezhman, Abdolvahed, Umi Kalthom, & Husniah, 2015). Nevertheless, these studies were focusing more on the influence of age, gender, marital status and school type on teacher burn-out, and little analytic attention has been paid to those who serve in rural schools.…”
Section: The Burnout Phenomenon Among Rural English Teachersmentioning
confidence: 99%
“…It should be noted that the environment of the workplace in which the teacher teaches may somehow affect the way the teaching and learning process takes place, and the locality aspect like rural areas is taken into consideration (Suliman & Yunus, 2014). Also, noted issues faced by English teachers at risk of or already burned out were high levels of stress (Mahboobeh et al, 2012;Mukundan & Khandehroo, 2010;Mukundan et al, 2015). Abdullah, Uli and Salahudin (2007) argued that poor working conditions, especially in rural areas, contributed to low morale and dissatisfaction, which lead to teachers stress.…”
Section: The Burnout Phenomenon Among Rural English Teachersmentioning
confidence: 99%
“…Teaching is a gratifying yet very challenging profession. It is characterized by long and heavy hours of work that prevent teachers from taking care of their physical and mental well-being [15]. They are often left alone in large classes with a lot of prescription on what they should be teaching, requiring a high standard of efficiency and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The most apparent reason for teachers' departure is the burnout phenomenon. The existing literature disclosed that the level of burnout among English language teachers is significantly high (Mukundan et al, 2015) as they experience a high level of stressors in rural schools. Although the stressors are generally substantial to all teachers, they are particularly intense for those serving in rural schools (Aziz, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is supported by the data obtained from Sabah Education Department (2016), which revealed that most English teachers serving in rural schools are novice teachers who have just graduated less than two years. These inexperienced young novice teachers contribute to the lack of teacher quality (Aziz, 2015;Alice & Zuraidah, 2020) due to being more vulnerable to both emotional exhaustion and depersonalisation lead to burnout (Mukundan et al, 2015). Novice teachers often do not feel adequately prepared for the challenges in their first few years of teaching (Paronjodi et al, 2017) and need more support and experience to build up their quality.…”
Section: Literature Reviewmentioning
confidence: 99%